The Religious Aspect in the Transformation of the Autobiographical Image of Mlle de Montpensier (Proceedings of Southern Federal University. Philology, 2017)
Svetlana Yu. Pavlova (Saratov, Russian Federation)The article considers how Mlle de Montpensier’s (1627 – 1693) religious feeling developed in the course of work on the Memoirs and how it impacted the autobiographical image. The image is not created with the focus on the religious confession, but with the emphasis on the description of a worldly lifestyle of a person remaining true to Christian commandments. The author’s affection to the order of Carmelites is explained as well as the reasons of rejecting the life at the nunnery. It is shown how the memoire writer interprets the idea of a divine miracle as related to the protagonist image, and how she arrives at the stoic acceptance of her fate.Key words: memoirs, XVII-th century French Literature, Mademoiselle de Montpensier, autobiographical image, religiousness.DOI 10.23683/1995-0640-2017-3-19-27